KEABSAHAN PERKAWINAN BEDA AGAMA DI INDONESIA TERKAIT PENETAPAN NOMOR 916/PD.P/2022/PN SBY - Erda Rahmayanti Sitinjak; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Indonesia is a country with a multi-religious society, which opens up thepotential for interfaith marriages. The rules regarding marriage in Indonesia arecontained in Law No. 1 of 1974 concerning Marriage. It is still a matter of debatethat there is not a single article that clearly mentions interfaith marriages.Surabaya District Court with Determination Number 916/Pdt.P/2022/PN Sby ingranting the request for dispensation for interfaith marriages. The formulation ofthe problem of this research is what is the validity of interfaith marriages relatedto Determination Number 916/Pdt.P/2022/PN Sby and what are the legalconsequences of registering interfaith marriages with the Surabaya PN DecreeNumber 916/Pdt.P/2022/PN Sby. Purpose of writing This is to find out the validityof interfaith marriages related to Determination Number 916/Pdt.P/2022/PN Sbyaccording to Law Number 1 of 1974 concerning Marriage and to find out thelegal consequences of registering interfaith marriages with DeterminationNumber 916/Pdt.P/ 2022/PN Sby. This research is normative research using anapproach to the legal principles in Law Number 1 of 1974 concerning Marriage.From the research results, it can be concluded based on the analysis of thelegal materials obtained that according to the marriage law in Indonesia,interfaith marriages are prohibited and declared invalid and religiously, but theirregistration is valid according to state law. Based on the Surabaya DistrictCourt's determination that the legal consequences of registering a marriage arethat the status of the marriage is legally valid so that the relationship between ahusband and wife who give birth to a child through an interfaith marriage meansthe child has a legal status and is legally recognized.Keywords : Keywords: Marriage, different religions, validity, registration.